The Ectomycorrhizospheric Habitat of Norway Spruce and Tricholoma vaccinum: Promotion of Plant Growth and Fitness by a Rich Microorganismic Community - Wagner, Katharina; Krause, Katrin; Gallegos-Monterrosa, Ramses; Sammer, Dominik; Kovács, Ákos T.; Kothe, Erika (Frontiers in Microbiology, 2019)
The contribution of the mycorrhizospheric microbes in a stand of ectomycorrhizal Norway spruce (Picea abies) featuring mycorrhiza with the basidiomycete Tricholoma vaccinum was addressed by microbiome analysis and in vitro reconstruction of microbial as well as plant-microbe interactions. The protective role of the mycorrhizal fungus with respect to pathogen attack could be validated against Botrytis cinerea and Heterobasidion annosum in co-cultures revealing reduced pathogen growth, higher survival rate of the spruce trees and reduced symptoms on needles upon symbiosis with T. vaccinum. The community structure was shown to yield a high diversity in ECM forming basidiomycetes of Thelephorales and Agaricales associated with a rich bacterial diversity dominated by Rhizobiales with the most abundant Nitrobacter winogradski (3.9 %). Isolated bacteria were then used to address plant growth promoting abilities, which included production of the phytohormone indole-3-acetic acid (performed by 74 % of the bacterial isolates), siderophores (22 %), and phosphate mobilization (23 %). Among the isolates, mycorrhiza helper bacteria were identified, with Bacillus cereus MRZ-1 inducing hyperbranching in T. vaccinum, supporting tree germination, shoot elongation, and root formation as well as higher mycorrhization rates. Thus, a huge pool of potential mycorrhiza helper bacteria and fungal community with widely distributed auxin-production potential extended the ability of T. vaccinum to form ectomycorrhiza. The forest community profited from the mycorrhizal fungus T. vaccinum, with spruce survival enhanced by 33 % in microcosms using soil from the native habitat. A higher fungal abundance and diversity in cases where the tree had died during the experiment, showing that decomposition of plant litter from a dead tree supported a different community. T. vaccinum thus actively structured the community of microorganisms in its habitat.